Fishing in turbulent waters: resilience, risk, and trust in British Columbia's declining commercial salmon fishery - Elias del Valle; Benjamin Neal; Ilse Martínez-Candelas; Patrick Dann; Dawn Webb; Loren McClenachan (Canadian Science Publishing, 2024)
The impacts fishing communities face as a result of declining fisheries productivity and access may largely hinge on measurable attributes of their social resilience. Wild-origin Pacific salmon populations have been in a marked decline since the 1960s, resulting in progressively declining access for many commercial fisheries. More recent acute stressors have caused appreciable tribulation to commercial fishers in British Columbia, raising concern over their capacity to remain viable in the industry, and underscoring the need to examine the fishery under a social resilience framework. Here, we coupled an online survey instrument with in-depth interviews to assess commercial salmon fishers' social resilience, socioeconomic characteristics, risk perceptions, trust in fishery management, and the relationships between these variables. Our results show that social resilience is low overall, with older, more experienced, and less diversified fishers being particularly vulnerable to declining salmon access. While 73% of fishers reported having plans to adapt to future declines in salmon access, 92% reported feeling that there are barriers impeding their adaptation, and 75% reported having no trust in fisheries management helping them adapt. Fishers' social resilience was positively correlated with their trust in, and perceived trust from fisheries management.